Nondestructive in situ monitoring of pea seeds germination using optical coherence tomography. (12th July 2022) - Li, Xinhua; Yang, Xingyu; Li, Xiaoran; Zhao, Zhiyi; Zhang, Zijian; Lin, Hungyen; Kang, Dingming; Shen, Yaochun
Abstract: Seed germination and uniform plant stand in the field are the most critical crop growth stages determining the final yield. Pea ( Pisum sativum L .) seeds production is often hampered due to the seed dormancy caused by the hard seed coat. Such effect is mainly attributed to poor or uneven germination and unsynchronised seedling emergence. Understanding the time course of water intake and several critical germination indicators can reveal many features of seed germination such as rate and uniformity. This paper used optical coherence tomography (OCT), a noninvasive and cross‐sectional imaging technique, to monitor the inner structural changes throughout the germination process. A sequence of cross‐sectional OCT images of pea ( P. sativum L .) seeds, together with additional microscopic optical images, was recorded continuously and in situ for over 40 h. OCT and microscopic images revealed the changes in the internal structure and the external shape of the pea seeds during germination, respectively. It was found that the cross‐sectional OCT images helped to identify the critical indicators distinguishing the different phases of germination pea seeds. Therefore, the presented OCT approach offers a fast and nondestructive way to precisely measure the structural indicators in different germination phases.